2021
DOI: 10.3390/jcm10122608
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors of Infection, Hospitalization and Death from SARS-CoV-2: A Population-Based Cohort Study

Abstract: We conducted a prospective population-based cohort study to assess risk factors for infection, hospitalization, and death from SARS-CoV-2. The study comprised the people covered by the Health Service of Navarre, Spain. Sociodemographic variables and chronic conditions were obtained from electronic healthcare databases. Confirmed infections, hospitalizations, and deaths from SARS-CoV-2 were obtained from the enhanced epidemiological surveillance during the second SARS-CoV-2 epidemic surge (July–December 2020), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
45
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(59 citation statements)
references
References 26 publications
(43 reference statements)
8
45
0
6
Order By: Relevance
“…Although we did not have specific information about their occupations, we speculate that mothers with higher education may be less likely to be employed in service-related jobs and more likely to engage in remote work, which may have reduced their potential for virus exposure. Consistent with previous research that reported a higher risk of COVID-19 infection among immigrants [ 13 , 14 ], our data demonstrated a significantly increased risk of COVID-19 test positivity among foreign-born mothers independent of the effects of age, education, obesity, and chronic medical conditions. Although the exact mechanism underlying this association is unknown, we hypothesize that this is likely due to a combination of social risk factors of COVID-19 exposure and infection shown to be prevalent in foreign-born populations, such as exposure to overcrowded living environments, higher incidence of poverty, and employment in high exposure/contact jobs (i.e., to provide essential services such as health care, or at essential businesses like grocery stores, etc.)…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Although we did not have specific information about their occupations, we speculate that mothers with higher education may be less likely to be employed in service-related jobs and more likely to engage in remote work, which may have reduced their potential for virus exposure. Consistent with previous research that reported a higher risk of COVID-19 infection among immigrants [ 13 , 14 ], our data demonstrated a significantly increased risk of COVID-19 test positivity among foreign-born mothers independent of the effects of age, education, obesity, and chronic medical conditions. Although the exact mechanism underlying this association is unknown, we hypothesize that this is likely due to a combination of social risk factors of COVID-19 exposure and infection shown to be prevalent in foreign-born populations, such as exposure to overcrowded living environments, higher incidence of poverty, and employment in high exposure/contact jobs (i.e., to provide essential services such as health care, or at essential businesses like grocery stores, etc.)…”
Section: Discussionsupporting
confidence: 92%
“…Notably, our study showed a lower risk of COVID-19 test positivity in smokers. Although similar findings have been found in previous studies [ 3 , 8 , 13 ], this result should be considered carefully due to the smoking status in our study reflecting the status during index pregnancy, not current.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Moreover, the range of factors examined by these retrospective or cross-sectional studies was rather limited. Factors significantly or non-significantly associated with Covid-19 were sex 1 , age 1 , ethnicity 2 , urbanisation 3 , residence in a multifamily unit 4 , BMI and obesity 2,5,6 , smoking 2,7 , physical fitness and forced expiratory volume 2 , the number of daily contacts 3 , wearing masks and washing hands 3 , socioeconomic deprivation 2 , particular AB0 blood groups [8-10], Rh factor [10], vitamin D deficiency [11], high-density lipoprotein level 2 , use of immunosuppressants 8 , and a growing set of comorbidities – cardiovascular disease, chronic obstructive pulmonary disease (COPD), chronic kidney disease, dementia, hypertension and functional dependence 6 , and toxoplasmosis 9 . Other factors, such as contact with animals, have been suggested only on a theoretical basis 10 or are merely discussed in non-scientific sources, such as popular literature or the internet.…”
Section: Introductionmentioning
confidence: 99%